Effectiveness of the Telemedicine Approach on Maternal Health Practices among Pregnant Women in Rural Areas - Bonifasius; Kayika, I Putu Gede; abdul madjid, omo; Seno Adjie, Josef Maria; Marceliano Rumopa, Harold Immanuel (Indonesian Journal of Obstetrics and Gynecology, 2024)
Objectives: To systematically evaluate the current evidence on the effectiveness of the telemedicine approach on maternal practices in rural communities. The author hopes that this study offers a breakthrough to draw a solid conclusion regarding the feasibility of implementing telemedicine to improve maternal health in rural areas of Indonesia.Methods: A systematic literature search was performed using international databases, such as Cochrane, PubMed, EBSCOhost, Science Direct, Scopus, and Google Scholar, published from 2012 to August 31, 2022. Risk of bias assessment was conducted using the Cochrane Risk of Bias tools 2.0 for randomized controlled trials and converted to the AHRQ standards.Results: This study included five randomized controlled trials from different countries, namely India, Ethiopia, and Kenya. Telehealth interventions, delivered using mobile applications, phone calls, or short text messaging, improved the number of ANC visits, safe childbirth in hospitals or by skilled staff, exclusive breastfeeding, and immunization compliance, with a significant difference compared to the control group that received no intervention (p<0.05). Nevertheless, considering the already widely used mobile phone technologies in rural settings, it is now clear that the telehealth approach should be scaled up and implemented in clinical settings.Conclusion: Telehealth-based intervention is a promising approach to promote better maternal health practices among pregnant mothers in rural and low-resources settings. This approach has been proved to successfully made a significant difference in terms of antenatal care visits and safe childbirth practice.Keywords: Maternal health practices, pregnant women, rural areas, systematic review, telemedicine.